2016
DOI: 10.5114/bta.2016.60778
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage synthesis by in vitro cell culture in different species of Alyssum

Abstract: Mucilage is a class of polysaccharides found in some plants that have pharmaceutical effects as anti-hemorrhoids.Alyssum is one such species; its seeds produce mucilage that possesses pharmaceutical properties. The aim of this study was to optimize the conditions for callus production and mucilage synthesis in Alyssum species in a tissue culture procedure. In the study presented here, callus initiation in different genotypes of Alyssum species (A. inflatum, A. lepidium, and A. strigosum) has been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…Mucilage was extracted from freeze-dried T2 calli alongside mature seeds. In line with previous findings 9,10,16 , the mass yield of material extracted from calli exceeded that extracted from seed in both species, but yield from both types of callus was comparable ( Figure 3A). As mucilage is predominantly polysaccharide 1 , monosaccharide profiling was used to assess the composition of callus-derived extracted material ( Figure 3B and 3C).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Mucilage was extracted from freeze-dried T2 calli alongside mature seeds. In line with previous findings 9,10,16 , the mass yield of material extracted from calli exceeded that extracted from seed in both species, but yield from both types of callus was comparable ( Figure 3A). As mucilage is predominantly polysaccharide 1 , monosaccharide profiling was used to assess the composition of callus-derived extracted material ( Figure 3B and 3C).…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that mucilage produced from mucilaginous calli can be easily extracted to yield quantities significantly higher than seedderived mucilage. Recent work reported that calli derived from Plantago lanceolata 9 , P. ovata 10,11 , P. major 12 , Lepidium sativum 13,14 , Linum usitatissimum 15 and several Alyssum species 16 could produce significantly (up to 10) more mucilage than their respective…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated explants and plant growth-regulator concentrations at high mucilage synthesis by employment of desirable genotype. Our findings are consistent with those of Gupta et al [7], Mirmasumi et al [22] and Afshar and Golkar [29] who have obtained relatively large amount of mucilage compound as a secondary metabolite in undifferentiated calli of P. ovata, P. lanceolata and Alyssum species, than the seeds obtained by field grown plants, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…The significant genetic variation observed for callusrelated traits. The genotypic dependence of callus growth rate were supported by previous studies on P. ovata [18] and P. major [29]. Moreover, CGR has been shown to be a strong genetic component in the callus cultures [30].…”
Section: Discussionsupporting
confidence: 65%